Monas sebagai Wajah Dewasa Kota Jakarta: Analisis Manajemen Reputasi dalam Pengelolaan Monas sebagai Ikon Negara - Bhernadetta Pravita Wahyuningtyas (Humaniora, 2012)
Article explains the management of Monumen Nasional (Monas)’s reputation, an Icon of Jakarta as well as a symbol of Indonesia. The study used post positivist paradigm, the nature of the study was descriptive and the selected approach was qualitative. Data compilation was done by in-depth interviews and observation, narrative analysis was applied. The aim of this study was to review the management of reputation of MONAS in its golden age. It can be concluded that Monas as an iconic monument or a symbol of Indonesia is improving continuously, therefore the people could be proud of it. The reputation management of MONAS is the results of coordination and socialization process within the institution, because the reputation achieved through cooperation of each department, and could not be achieved without communication.